IC 9469 - Design And Testing Of A Nondestructive Friction Bolt Tester - Lewis Martin; John Goris; Lauren Roberts (The National Institute for Occupational Safety and Health (NIOSH), 2004)
The Spokane Research Laboratory (SRL) of the National Institute for Occupational Safety and Health (NIOSH) and Thiessen Team USA, Spokane, WA, have developed a pull claw that can be attached to any accessible friction bolt ring to test the performance (i.e., load-carrying capacity) of bolts without the use of a pull collar. This would allow true random testing of friction bolts, which need to be evaluated to determine if they are still providing an adequate level of support months or years after installation. Such support is critical to maintaining safe working conditions for underground miners.